2022
DOI: 10.57235/aurelia.v1i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Debt To Equity Ratio dan Pertumbuhan Aset Terhadap Kinerja Keuangan pada Perusahaan Industri Pertahanan Indonesia

Abstract: AbstrakUntuk mengembangkan industri pertahanan dalam negeri perlu diberlakukan kebijakan pembangunan industri pertahanan guna mewujudkan industri pertahanan yang kuat, mandiri, dan dapat memiliki daya saing untuk mendukung pertahanan dan keamanan serta berkontribusi terhadap pertumbuhan ekonomi nasional. Untuk memajukan Industri pertahanan dalam negeri perlu ditinjau aspek keuangan dimana kinerja perusahaan dapat digambarkan dari laporan keuangannya, hal tersebut diperlukan untuk mengukur keberhasilan kinerja … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, companies with a low DER tend to create higher ROE, due to lower financial burdens, and vice versa. This study contradicts the research conducted by Hidayat et al (2022), andWiranawata (2022), but is aligned with the study by Lestari (2020).…”
Section: Hypothesis Testing (H4)contrasting
confidence: 85%
See 1 more Smart Citation
“…Therefore, companies with a low DER tend to create higher ROE, due to lower financial burdens, and vice versa. This study contradicts the research conducted by Hidayat et al (2022), andWiranawata (2022), but is aligned with the study by Lestari (2020).…”
Section: Hypothesis Testing (H4)contrasting
confidence: 85%
“…On the other hand, if a company heavily relies on borrowing, higher interest expenses may erode the net profit. Drawing from the findings of the research carried out by Gunawan et al (2022); Hidayat et al (2022); and Wiranawata (2022), it is suggested that DER serves as a favorable indicator of capital structure that can positively impact company performance. However, there are contrasting findings from other studies, including those by Ghardallou (2022); Irman et al (2020);and Sukesti et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Not only does it require good planning, but also an effective and efficient financial system and budget in building the defense industry (Hidayat et al, 2022). In reviewing the development of a company, one can see it through its financial aspects which can be projected in financial reports (Nugraha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%